Loneliness, social isolation and incident chronic kidney disease among patients with diabetes - Xiang Li; Yoriko Heianza; Lu Qi; Hao Ma; Jian Zhou; Xuan Wang; Rui Tang (General Psychiatry)
Background Individuals with diabetes have a significantly higher risk of developing chronic kidney disease (CKD) and higher levels of social isolation and loneliness compared with those without diabetes. Recently, the American Heart Association highlighted the importance of considering social determinants of health (SDOH) in conjunction with traditional risk factors in patients with diabetes.Aims To investigate the associations of loneliness and social isolation with incident CKD risk in patients with diabetes in the UK Biobank.Methods A total of 18 972 patients with diabetes were included in this prospective study. Loneliness and Social Isolation Scales were created based on self-reported factors. An adjusted Cox proportional hazard model was used to investigate the associations of loneliness and social isolation with CKD risk among patients with diabetes. The relative importance in predicting CKD was also calculated alongside traditional risk factors.Results During a median follow-up of 10.8 years, 1127 incident CKD cases were reported. A higher loneliness scale, but not social isolation, was significantly associated with a 25% higher risk of CKD, independent of traditional risk factors, among patients with diabetes. Among the individual loneliness factors, the sense of feeling lonely emerged as the primary contributing factor to the elevated risk of CKD. Compared with individuals not experiencing feelings of loneliness, those who felt lonely exhibited a 22% increased likelihood of developing CKD. In addition, feeling lonely demonstrated greater relative importance of predicting CKD compared with traditional risk factors such as body mass index, smoking, physical activity and diet.Conclusions This study indicates the significant relationship between loneliness and CKD risk among patients with diabetes, highlighting the need to address SDOH in preventing CKD in this population.